2021
DOI: 10.3390/cells10102737
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Distribution Width Is Associated with P-Selectin Dependent Platelet Function: Results from the Moli-Family Cohort Study

Abstract: Defined as an index of platelet size heterogeneity, the platelet distribution width (PDW) is still a poorly characterized marker of platelet function in (sub)clinical disease. We presently validated PDW as a marker of P-selectin dependent platelet activation in the Moli-family cohort. Platelet-bound P-selectin and platelet/leukocyte mixed aggregates were measured by flow cytometry in freshly collected venous blood, both before and after in vitro platelet activation, and coagulation time was assessed in unstimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Decreased PDW is associated with decreased platelet activity and thus decreased thrombogenicity. 16 Moreover, Cfz led to an increased ADAM-TS13 activity and increased cleavage of vWF ( Figure S3B-D ). Since TMA is associated with decreased ADAM-TS13 activity, which leads to decreased vWF cleavage, 17 it seems that TMA does not contribute to the molecular mechanism of Cfz’s nephrotoxicity in mice.…”
Section: Resultsmentioning
confidence: 90%
“…Decreased PDW is associated with decreased platelet activity and thus decreased thrombogenicity. 16 Moreover, Cfz led to an increased ADAM-TS13 activity and increased cleavage of vWF ( Figure S3B-D ). Since TMA is associated with decreased ADAM-TS13 activity, which leads to decreased vWF cleavage, 17 it seems that TMA does not contribute to the molecular mechanism of Cfz’s nephrotoxicity in mice.…”
Section: Resultsmentioning
confidence: 90%
“…In perspective, additional studies are required to (i) precisely assess the risk of IFIs occurring in patients treated with ibrutinib and, more importantly, with other BTKis; (ii) disclose whether the multifunctional impairment in innate immunity is strictly caused by the inhibition of BTK outside the BCR (i.e., on unwanted cellular targets expressing BTK) or, more likely, is also mediated by unselective molecular inhibition of other kinases (such as TEC); (iii) fully characterize platelet proteomic and structural modifications occurring in the presence of BTKis; and (iv) test new immunological tools and specific inflammatory biomarkers, including platelet parameters, such as mean platelet volume (MPV) and platelet distribution width (PDW) [68,69], aiming to identify and monitor 'protective vs. permissive' immune profiles in patients with or at risk for IFIs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirmed a straight-line relationship between admission PDW and postoperative pneumonia in patients with AAAD and demonstrated that high PDW was significantly associated with an increased risk of postoperative pneumonia in patients with AAAD after adjustment for potential confounders. PDW, routinely measured by automated cell counters, has emerged as a relatively reliable marker of thrombopoiesis and platelet function (18). PDW is used to reflect the variability in platelet size and detect fractions of larger platelets that are more active, both enzymatically and metabolically (8).…”
Section: Discussionmentioning
confidence: 99%
“…PDW, routinely measured by automated cell counters, has emerged as a relatively reliable marker of thrombopoiesis and platelet function ( 18 ). PDW is used to reflect the variability in platelet size and detect fractions of larger platelets that are more active, both enzymatically and metabolically ( 8 ).…”
Section: Discussionmentioning
confidence: 99%